Topics on Methodological and Applied Statistical Inference 2016
DOI: 10.1007/978-3-319-44093-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Bounding the Probability of Causation in Mediation Analysis

Abstract: Given empirical evidence for the dependence of an outcome variable on an exposure variable, we can typically only provide bounds for the "probability of causation" in the case of an individual who has developed the outcome after being exposed. We show how these bounds can be adapted or improved if further information becomes available. In addition to reviewing existing work on this topic, we provide a new analysis for the case where a mediating variable can be observed. In particular we show how the probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The bounds we obtained for the value of PC is exactly the same as shown by Dawid [1,4]. Pearl uses a different notation, but the values are exactly the same under specific conditions, as was mentioned in [3].…”
Section: Comparing the Results With The Formulas Given By Dawid And P...supporting
confidence: 56%
See 3 more Smart Citations
“…The bounds we obtained for the value of PC is exactly the same as shown by Dawid [1,4]. Pearl uses a different notation, but the values are exactly the same under specific conditions, as was mentioned in [3].…”
Section: Comparing the Results With The Formulas Given By Dawid And P...supporting
confidence: 56%
“…While Pearl approached the problem from a structural equation modeling perspective, Dawid [9] ap-proached the problems from concept similar to a joint distribution over the different cause-effect situations. In his later works [1,4], Dawid has worked on defining the limits of PC under various confounding and mediation scenarios. Here we are not concerned with the philosophical aspects of causation in objective reality as these, as clearly demonstrated by Kant [10] can never be ascertained with certainty, but with issues arising when applying the formalisms developed in this domain to practical problems.…”
Section: Brief Historymentioning
confidence: 99%
See 2 more Smart Citations
“…which is a testable implication of our assumptions. We For the case that M is observed in the experimental data, but not for Juanita, Dawid et al (2016) showed that this additional information does not change the lower bound l on PC in (30), but does lower the upper bound, u. Dawid & Musio (2021) extend this analysis to cases with additional covariates, while Dawid et al (2019) deal with the case that we have a complete mediation sequence X = M0 → M1 → • • • → Mn−1 → Mn = Y , and know the probabilistic structure of each link in the chain; with all, some, or none of the M s being observed for Juanita.…”
Section: Mediatorsmentioning
confidence: 88%